Upacara Autotu Nimoe (Pemakaman Mayat) Sebagai Proses Pembelajaran Teologi Hindu Pada Masyarakat Etnik Nuaulu Kampung Lama, Desa Sepa, Kabupaten Maluku Tengah - Wanasia Peririsia; Anak Agung Oka Puspa; I Made Sutresna (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2022)
This study discusses the understanding of the Autotu Nimoe (corpse burial) ceremony as a learning process for the Hindu theology of the Nuaulu ethnic group in Lama village, Sepa village, Central Maluku district. This study discusses the understanding of the Nuaulu ethnic community towards the form, meaning and function of the Autotu Nimoe (corpse burial) ceremony. This study aims to determine the understanding of the ethnic community of Nuaulu Autotu Nimoe Ceremony (corpse burial). In this study using an approach approach, with interview and library techniques. The results of the study reveal that the Autotu Nimoe (corpse burial) ceremony is still applied by the Nuaulu ethnic community until now in the same form. The understanding of the Nuaulu ethnic community about this ceremony is that it has been carried out by ancestors from ancient times.